Pressure Injury Prevention in COVID-19 Patients With Acute Respiratory Distress Syndrome - Team, Victoria; Team, Lydia; Jones, Angela; Teede, Helena; Weller, Carolina D. (Frontiers in Medicine, 2021)
Coronavirus Disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was identified in China in December 2019 and became pandemic in a short period of time. While most infected people might have mild symptoms, older people and people with chronic illnesses may develop Acute Respiratory Distress Syndrome (ARDS). Patients with ARDS with worsening hypoxaemia require prone positioning to improve respiratory mechanics and the oxygenation. Intubated patients may stay in a prone position up to 12-16 hours, increasing the risk of pressure injury (PI). Frequent skin inspections and PI risk assessment in COVID-19 patients will be challenging due to hospital infection control measures aimed to reduce the risk for health professionals. In this perspective article, we summarize the best practice recommendations for prevention of PI in SARS-CoV-2 infected ARDS patients in the prone positioning. Prior to positioning patients in prone position, the main recommendations are to: 1) conduct skin assessment; 2) use pressure redistribution devices; 3) select an appropriate mattress or an overlay; 4) ensure the endotracheal tube securing devise is removed and the endotracheal tube is secured with tapes; 5) use a liquid film-forming protective dressing; and 6) lubricate eyes and tape close. Once patient is prone, it is recommended to: 1) use the swimmer’s position; 2) reposition patient every two hours; and 3) keep the skin clean. When the patient is repositioned to supine position, health care professionals are advised to: 1) assess the pressure points and 2) promote early mobilization.